New Insights toward Colorectal Cancer Chemotherapy Using Natural Bioactive Compounds - Redondo-Blanco, Saúl; Fernández, Javier; Gutiérrez-del-Río, Ignacio; Villar, Claudio J.; Lombó, Felipe (Frontiers in Pharmacology, 2017)
Combination therapy consists in the simultaneous administration of a conventional chemotherapy drug (or sometimes, a radiotherapy protocol) together with one or more natural bioactives (usually from plant or fungal origin) of small molecular weight. This combination of anticancer drugs may be applied to cell cultures of tumor cells, or to an animal model for a cancer type (or its xenograft), or to a clinical trial in patients. In this review, we summarize current knowledge describing diverse synergistic effects on colorectal cancer cell cultures, animal models and clinical trials of various natural bioactives (stilbenes, flavonoids, terpenes, curcumin and other structural families), which may be important with respect to diminish final doses of the chemotherapy drug, although maintaining its biological effect. This is important as these approaches may help reduce side effects in patients under conventional chemotherapy. Also, these molecules may exerts their synergistic effects via different cell cycle pathways, including different ones to those responsible of resistance phenotypes: transcription factors, membrane receptors, adhesion and structural molecules, cell cycle regulatory components and apoptosis pathways.